MANAJEMEN KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH DASAR ISLAM TERPADU (SD IT) HARAPAN MULIA PALEMBANG - Amilda Amilda (El-Idare, 2016)
This study aimed to describe and analyze the management of IT curriculum in PAI elementary of Harapan Mulia Palembang and supporting and inhibiting factors. This research is a qualitative study using a case study approach. Informants in this study is the vice principal areas of curriculum, PAI teachers, and principals. The technique of collecting data through interviews, observation and documentation study nonparticipant. Data analysis technique using analytical techniques Miles and Huberman which includes data collection, data reduction, data presentation and conclusion. The results showed that: (1) management of IT curriculum in PAI elementary of Harapan Mulia Palembang include planning activities such as drafting curriculum PAI program, organizing the curriculum PAI PAI curriculum implementation, curriculum supervision PAI. (2) Factors supporting the implementation of the curriculum management PAI includes the availability of facilities such as facilities and infrastructure, intelligence possessed by learners, teacher competence and professionalism of teachers in teaching, as well as the additional hours of study / mulok supporting learning programs PAI such as literacy Al -Qur'an and others, the inhibiting factor is the difficulty of transferring the PAI subjects to the students, there are some students who have problems in class and the lack of readiness of teachers when teaching schedule has been determined.